Assessment of Long-Term Postoperative Pain in Open Thoracotomy Patients: Pain Reduction by the Edge Closure Technique - Sakakura, Noriaki; Usami, Noriyasu; Taniguchi, Tetsuo; Kawaguchi, Koji; Okagawa, Takehiko; Yokoyama, Megumi; Yokoi, Kohei (The Annals of Thoracic Surgery, 2010)
Long-term postoperative pain in open thoracotomy patients could be related to injured intercostal nerves, and several methods have been devised to protect these nerves. We retrospectively reviewed 184 consecutive patients who underwent posterolateral or anteroaxillary thoracotomy. Postoperative pain was routinely evaluated using an 11-point numerical pain rating scale (0 [no pain] to 10 [most severe pain]) at 1 to 2 weeks; 2 weeks to 1 month; and 1 to 2, 2 to 4, 4 to 6, 6 to 9, and 9 to 12 months after surgery. The following steps were considered to protect the intercostal nerves. During chest retraction, an intercostal muscle flap was harvested before using the retractor to prevent compression of the cranial intercostal nerve in posterolateral thoracotomy patients who needed buttressing of the bronchial stump. During closure, the thin space between the inferior edge of caudal rib and the intercostal neurovascular bundle was sutured to prevent strangulation of the intercostal nerve and vessels on the caudal side (edge closure technique). Subjects included 141 posterolateral and 43 anteroaxillary thoracotomies, 72 intercostal muscle flaps, and 87 conventional closures and 97 edge closures. During a year postoperatively, posterolateral thoracotomy patients experienced more pain (range, 1.2 to 4.6) than anteroaxillary thoracotomy patients (range, 1.1 to 3.7; p = 0.038 for all periods). Patients with the intercostal muscle flap tended to experience less pain than those without the flap during the first month postoperatively. The scores of patients having edge closure (range, 0.9 to 3.8) were significantly lower than those of patients undergoing conventional closure (range, 1.6 to 5.1; p < 0.001 for all periods). The edge closure technique, which preserved the caudal intercostal neurovascular bundle, successfully reduced pain.